MAKNA KOMUNIKASI WAYANG KULIT RARAS IRAMA DI BAGAN BATU KABUPATEN ROKAN HILIR - Agus Rio Candra; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Wayang is a shadow puppet show art that contains many elements of art, both music art, literature, craft (art) and others. The art of wayang kulit in Bagan Batu Rokan Hilir regency is under the community of transmigrants to continue to be preserved. Wayang kulit Raras Irama is the only leather puppets in Bagan Batu that are in great demand and interesting to study. The purpose of this research is to know the process communication of wayang kulit Rajas Irama and the meaning of wayang kulit Raras Irama in Bagan Batu Rokan Hilir This research uses qualitative method by using Symbolic Interaction theory. Subjects in this study were Dalang (trainer), Sinden, Music Player, people who invited wayang kulit and public (audience) performances chosen by Purposive sampling. Data collection techniques are done through observation, in-depth interviews and documentation. The results showed the communication process performances wayang kulit Raras Irama in Bagan Batu Rokan Hilir consists of performance preparations, shadow puppet performances and performance closures. The meaning of wayang kulit performance for Raras Irama wayang puppets includes puppeteer, sinden and music player. Dalang interpreted wayang kulit as self-expression, communication media and self-identity, sinden mean wayang kulit as cultural preservation and communication media and music player understood wayang kulit as cultural preservation and also communication media. The meaning of wayang kulit for the community that invites the show of Raras Irama wayang kulit in Bagan Batu Rokan Hilir regency as entertainment, education and interaction as well as self identity. The meaning of wayang kulit Raras Irama for the general public in Bagan Batu Rokan Hilir regency ie as entertainment and information. Keywords: Wayang kulit Raras Irama, Communication process, Meaning of communication, Symbolic interaction